2014
DOI: 10.1111/1755-5922.12060
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Medication Use Following Percutaneous Coronary Intervention: The Australian Experience

Abstract: SUMMARYAims: Despite the guidelines, a "treatment gap" exists in the delivery of pharmacotherapy for secondary prevention. We aimed to analyze the trend in guideline-based medication usage following percutaneous coronary intervention (PCI) using the Melbourne Interventional Group (MIG) registry over a 6-year period (2005)(2006)(2007)(2008)(2009)(2010). Methods: The MIG registry prospectively collects demographical, clinical, and procedural characteristics of consecutive patients undergoing PCI. We assessed med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…jg SCIENCE lipid-lowering agents) [29]. In Chile, 1 year after MI discharge, medication utilization from 6 public hospitals was aspirin 93%, clopidogrel 33%, beta-blockers 66%, ACEI/ARB 73%, and statins 85% [30].…”
Section: Clinical Setting and Duration Of Follow-upmentioning
confidence: 99%
“…jg SCIENCE lipid-lowering agents) [29]. In Chile, 1 year after MI discharge, medication utilization from 6 public hospitals was aspirin 93%, clopidogrel 33%, beta-blockers 66%, ACEI/ARB 73%, and statins 85% [30].…”
Section: Clinical Setting and Duration Of Follow-upmentioning
confidence: 99%
“…One recent Australian observational study reported outcomes of patients ( n  = 12813) following a percutaneous coronary intervention (PCI), the majority in the context of ACS [26]. In 2010, 75 % of patients were taking ≥ 4 classes of drugs at 12 month follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of medication prescription rates post-ACS report mostly high rates of antiplatelet therapy prescription [20, 26, 27, 31], with one study reporting an encouraging positive trend in medication prescription over time [26]. However, the prescription rates of other evidence-based medications demonstrate room for improvement, especially angiotensin-converting enzyme inhibitor/angiotensin-II receptor blockers (ACEi/ARBs) and glycerol trinitrate (GTN) spray [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, <50-year-old patients have an almost universal optimal medication at the time of hospital discharge from PCI. However, in general, 25-60% of patients discontinue optimal discharge medication one year after PCI (16)(17)(18). Moreover, young age in itself is a known predictor of both adverse events as well as poor adherence to secondary prevention (19,20).…”
Section: Discussionmentioning
confidence: 99%